Faktor-Faktor Yang Mempengaruhi Kebijakan Hutang Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi - Christie, Jessica; Nariman, Augustpaosa (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study was to determine the effect of liquidity, sales growth and profitability on the debt policies of manufacturing companies listed on the Stock Exchange in the consumer goods industry sector between 2018 and 2020. Sampling was carried out by purposive sampling for sample selection with 33 selected companies. The panel data regression model used is REM and tested using multiple linear regression. The results showed that there was a significant positive effect between profitability on debt policy, but liquidity had a significant negative effect on debt policy. There is no significant effect between sales growth on debt policy.